2007
DOI: 10.1253/circj.71.681
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Levels of Oxidized Low-Density Lipoprotein Relate to the Presence of Angiographically Detected Complex and Thrombotic Coronary Artery Lesion Morphology in Patients With Unstable Angina

Abstract: he role of inflammation in patients with acute coronary syndromes (ACS) is presently undisputed, supported by histopathological studies of unstable coronary plaque, 1 as well as clinical studies of elevated circulating acute-phase reactants. 2,3 Oxidized low-density lipoprotein (ox-LDL) is generally considered to be a key factor in the genesis of the inflammatory process in atherosclerotic lesions 4,5 and the detection of ox-LDL in human plasma has opened new avenues of the study of its relationship to the ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 30 publications
3
21
0
1
Order By: Relevance
“…Coronary heart disease was also associated with a higher ox-LDL/LDLcholesterol ratio, which is consistent with previous studies [2][3][4]. Women with cancer also had a higher ox-LDL/LDL-cholesterol ratio than women without cancer in this study, which is consistent with a previous study that showed elevated ox-LDL in women with breast or ovarian cancer [30].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Coronary heart disease was also associated with a higher ox-LDL/LDLcholesterol ratio, which is consistent with previous studies [2][3][4]. Women with cancer also had a higher ox-LDL/LDL-cholesterol ratio than women without cancer in this study, which is consistent with a previous study that showed elevated ox-LDL in women with breast or ovarian cancer [30].…”
Section: Discussionsupporting
confidence: 93%
“…Oxidized low-density lipoproteins (ox-LDL) are taken up by scavenger receptors on macrophages and contribute to the formation of foam cells and atherosclerotic lesions [1]. Elevated circulating ox-LDL are associated with more severe atherosclerotic lesions [2], and high circulating levels of ox-LDL have been shown to be independently predictive of subclinical atherosclerosis [3] and acute coronary heart disease [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because the number of subjects requiring cardiovascular risk stratification is extremely large, all of the methods of morphological and functional assessment of vascular damage cannot be used in all of the subjects. Thus, the establishment of efficient strategies for risk stratification using new serological markers, 89,90 the morphological markers of vascular damage and vascular function tests (ie, selecting the best one, the best combination, or all), in addition to assessment of the risk factors for CVD, is needed.…”
Section: Perspectives and The Next Stepmentioning
confidence: 99%
“…20 The plasma levels of oxLDL are related to the presence of angiographically detected complex and thrombotic lesion morphology in patients with unstable angina. 21 LOX-1 binding to oxLDL enhances nitric oxide (NO) catabolism as a result of superoxide generation, and decreases NO release via attenuated endothelial NO synthase (eNOS) activity. LOX-1 has been recently shown to form a complex with MT1-MMP under a basal condition.…”
Section: Lox-1 Signalingmentioning
confidence: 99%